A 10-month prospective study of organophosphorus pesticide exposure and neurobehavioral performance among adolescents in Egypt. (January 2016) - Rohlman, Diane S.; Ismail, Ahmed A.; Rasoul, Gaafar Abdel; Bonner, Matthew R.; Hendy, Olfat; Mara, Kristin; Wang, Kai; Olson, James R.
Abstract: Chlorpyrifos is an organophosphorus (OP) pesticide widely used around the world for agricultural operations. Although studies have examined exposure in children, there is limited information on adolescents who are occupationally exposed. Furthermore, there is limited research addressing the change in exposure patterns and outcomes across the application season. The goal of the current study was to examine the impact of chlorpyrifos exposure on neurobehavioral performance in adolescents before, during and after the application season. The longitudinal study was conducted in Egypt from April 2010 to January 2011, quantifying exposure and neurobehavioral performance with repeated measures prior to, during, and following the application period. At each test session, participants completed a neurobehavioral test battery and urine was collected for analysis of the chlorpyrifos metabolite 3, 5, 6-trichloro-2 pyridinol (TCPy) (biomarker of exposure). Cumulative urinary TCPy over the study period was used to classify participants into low (<median) and high (≥median) exposure groups. The urinary TCPy concentrations increased for both groups during the application season and decreased following the end of application. TCPy levels were significantly elevated in the high exposure group compared to the low exposure groups at all time intervals except baseline. Deficits in cumulative neurobehavioral performance were found among the high exposure group compared with the low exposure group. Additionally, changes in neurobehavioral performance across the application season indicate a pattern of impaired performance in the high exposure group compared to the low exposure group. Deficits increased during the application season and remained even months after application ceased. This study is the first to examine the impact of changes in pesticide exposure and neurobehavioral performance not only before and after the application season, but also within the application season. Furthermore, this study examines the impact of pesticide exposure on an adolescent population who may be at greater risk than adult populations.